Development of Learner Worksheets Based on PjBL Model to Increase Creativity on Material Changes in the Form of Objects - Sovi Ambarwati; Dwi Yulianti; Ryzal Perdana; Sugeng Sutiarso; Muhammad Nurwahidin (IJORER : International Journal of Recent Educational Research, 2024)
Objective: Creativity is the ability of individuals to express themselves so that they will produce new ideas and works. Creativity can be enhanced by creating innovative learning activities that encourage students to express themselves and provide creative ideas so that students' creativity continues to increase. This study aims to determine the development of PjBL-based SW, its attractiveness, and increased student creativity. Method: This research (R&D) uses the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Results: The results of this study indicate that 1) the product developed with the ADDIE model is declared "very valid." 2) PjBL-based SW obtained interesting results, and 3) PjBL-based SW has been proven to increase student creativity in a very creative category. Novelty: The novelty of this research is that the results of the independent thinking indicator are low when compared to other indicators, so these findings can be used as a basis for making research instruments on independent thinking for students' creativity.